Demographic and HIV‐specific characteristics of participants enrolled in the INSIGHT Strategic Timing of AntiRetroviral Treatment (START) trial. (April 2015) - Sharma, S; Babiker, AG; Emery, S; Gordin, FM; Lundgren, JD; Neaton, JN; Bakowska, E; Schechter, M; Wiselka, MJ; Wolff, MJ; ,
Abstract : Objectives: The risks and benefits of initiating antiretroviral treatment (ART) at high CD4 cell counts have not been reliably quantified. The Strategic Timing of AntiRetroviral Treatment (START) study is a randomized international clinical trial that compares immediate with deferred initiation of ART for HIV‐positive individuals with CD4 cell counts above 500 cells/μL. We describe the demographics, HIV‐specific characteristics and medical history of this cohort. Methods: Data collected at baseline include demographics, HIV‐specific laboratory values, prior medical diagnoses and concomitant medications. Baseline characteristics were compared by geographical region, gender and age. Results: START enrolled 4685 HIV‐positive participants from 215 sites in 35 countries. The median age is 36 years [interquartile range (IQR) 29–44 years], 27% are female, and 45% self‐identify as white, 30% as black, 14% as Latino/Hispanic, 8% as Asian and 3% as other. The route of HIV acquisition is reported as men who have sex with men in 55% of participants, heterosexual sex in 38%, injecting drug use in 1% and other/unknown in 5%. Median time since HIV diagnosis is 1.0 year (IQR 0.4–3.0 years) and the median CD4 cell count and HIV RNA values at study entry are 651 cells/μL (IQR 584–765 cells/μL) and 12 754 HIV RNA copies/mL (IQR 3014–43 607 copies/mL), respectively. Conclusions: START has enrolled a diverse group of ART‐naïve individuals with high CD4 cell counts who are comparable to the HIV‐positive population from the regions in which they were enrolled. The information collected with this robust study design will provide a database with which to evaluate the risks and benefits of early ART use for many important outcomes.